A Review on Super Resolution Based In painting (International Journal of Scientific Research and Management (IJSRM), 2017)
In this Paper, We study about Image interpolation technique and its applications. It is a technique of filling the gaps in an image. There are two types of algorithms available in web market. We had made some improvements to Exemplar based inpainting technique so as to overcome drawbacks such as computational complexity, noise and image structure. The Existing method introduces blur while in case of filling large holes and the advantage of proposed one can fill it without causing blur. First, we input an image which to be restored for some detail then to select the required region and now a single super resolution image is formed by sampling then with a series of low resolution image, it fills the required hole. Experimental results demonstrate the effectiveness of the proposed method.